Представить в виде многочлена 1 - (2а - 3)(а + 2)

masha2450 masha2450    2   24.02.2021 10:56    0

Ответы
janamelnik10 janamelnik10  24.02.2021 11:00

ответ:  -2а²-а+7

Объяснение:

1 - (2а - 3)(а + 2)=1-(2а²+4а-3а-6)=1-2а²-4а+3а+6= -2а²-а+7

ПОКАЗАТЬ ОТВЕТЫ
rpppppppyuv rpppppppyuv  24.02.2021 11:00

Объяснение:

Упростить многочлен:

1−(2a−3)(a+2)

1-(2а-3)(a+2)=

Раскрытие скобок:

1+(−2a+3)(a+2)=

Раскрытие скобок:

1−2a^2−4a+3a+6=7−2a^2−a=−2a^2−a+7

−2a^2−a+7

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра